MALIK IBN ANAS IBN MALIK DAN KITAB AL-MUWATHTHA’: INTRODUKSI BIOGRAFI DAN KARYA MONUMENTALNYA - Ulum, Khozainul (Akademika, 2017)
Islam has an extraordinary scientific treasure from all aspects, especially during its glorious era known as the golden age. At this time, many Islamic scholarships were systematically arranged and codified in the form of books, one of which is the science of hadith. This is due to the intensity and consistency of Islamic scholars to develop their knowledge. One of the scholars who gave his attention to the hadith was Malik ibnAnasibn Malik who codified the science of his hadith in the book called al-Muwaththa ', although the codification was at the request of the Caliph Abu Ja'far al-Manshur, one of the Abbasid Caliphs with the aim of being used as legislation (qanun) during the time of the Caliphate. What is interesting from the book of al-Muwaththa' is the systematic writing in which in his book Malik ibnAnasibn Malik included the called atsar from his friends and tabi'in. In fact, in the al-Muwaththa' hadith that are considered mursal, munqathi', mu'dlal and balaghat were also found, even though Malik ibnAnasibn Malik was very thorough and selective in the selection of hadith.Keywords: Malik ibnAnasibn Malik, al-Muwaththa'.